STRATEGI BAURAN PEMASARAN PRODUK GELATO: STUDI KASUS UMKM CV. YUMEDA PANGAN SEJAHTERA YOGYAKARTA - Nisa, Afifa Aulia; Kancana, Sauptika; Sugiarto, Meilan (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2020)
This study aims to formulate an alternative marketing mix strategy for gelato products for CV Yumeda Pangan Sejahtera. This research is descriptive research. Data collection was carried out through interviews and questionnaires. The research subjects were ten resource persons. Data analysis was carried out in 3 stages, at the input stage using the IFE and EFE matrices, then the matching stage using SWOT analysis, finally using the QSPM matrix. The results of the study showed an overview of the internal conditions of CV. Yumeda Pangan Sejahtera is relatively strong. Meanwhile, the external conditions faced were relatively strong. The results of the matching stage, CV. Yumeda Pangan Sejahtera is in Quadrant I in the grand strategy matrix, so it is advisable to carry out market and product development. The results of the SWOT analysis show that the dominant strategy is a product strategy through product development, a promotional strategy that emphasizes the promotion mix, and a distribution strategy by expanding distribution channels. At the decision stage, the QSPM matrix shows which strategy can be the best alternative to the business conditions of CV. Yumeda Pangan Sejahtera is a promotional strategy by emphasizing attention to the promotion mix. CV. Yumeda Pangan Sejahtera is expected to implement a promotional strategy by emphasizing sales promotion, advertising, sales force, public relations and direct marketing to increase sales turnover and be able to compete with competitors.